EVALUASI DAMPAK OPPORTUNISTIC WIRELESS ENCRYPTION (OWE) TERHADAP KINERJA JARINGAN NIRKABEL IEEE 802.11AX - Saputro, Vian Ardiyansyah; Jaenul, Ariep (Universitas Budi Luhur, 2025)
Security is a critical concern when using wireless networks, especially on open networks. Opportunistic Wireless Encryption (OWE) provides a solution to enhance protection on open wireless networks through encryption. This study evaluates the impact of OWE implementation on the performance of 802.11ax networks, focusing on metrics such as throughput and packet loss, compared to open security. An experimental approach was conducted in a client-server topology, measuring maximum throughput using the TCP protocol with packet sizes of 384 KB, 640 KB, and 1408 KB. Packet loss was also measured using the UDP protocol with data sizes of 10 MB, 100 MB, and 1000 MB. The results indicate that using OWE leads to performance degradation as packet size increases. Throughput decreases by 5–10 Mbps compared to open security, while the highest packet loss of 16% occurs with a bandwidth of 100 MB. These findings highlight that the encryption overhead in OWE affects performance, particularly with larger packet sizes. Despite the performance impact, OWE significantly enhances the security of open networks. However, the trade-off between performance and security should be carefully considered when implementing OWE in practical scenarios.